2012
DOI: 10.1177/0017896912446553
|View full text |Cite
|
Sign up to set email alerts
|

Implementation process and acceptance of a setting based prevention programme to promote healthy lifestyle in preschool children

Abstract: Objective: Evaluation of the implementation process of a kindergarten-based intervention ('TigerKids') to promote a healthy lifestyle. Design: Questionnaire survey among kindergarten teachers about programme implementation and acceptance. Setting: Kindergartens in Bavaria, Germany. Methods: Two hundred and fifteen kindergartens were included; 96.3 % returned informative questionnaires. 'TigerKids' is a multi-approach behavioural intervention programme to increase physical activity level and to promote healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…SHAPES intervention delivery improved over the 3 years, possibly due to teacher experience, interventionist experience, and/or the time needed for organizational change to take place. As is commonly reported in the literature (Alhassan & Whitt-Glover, 2014;Finch et al, 2014;Herbert et al, 2013), variability in implementation occurred over time for a given teacher and within a given school at any point in time. This variability suggests that classroom-and school-level factors influenced preschool teacher implementation, which we are investigating as a reflection of setting complexity (Craig et al, 2008;Foster-Fishman, Nowell, & Yang, 2007;Hawe, Shiell, & Riley, 2004.…”
Section: Discussionmentioning
confidence: 82%
“…SHAPES intervention delivery improved over the 3 years, possibly due to teacher experience, interventionist experience, and/or the time needed for organizational change to take place. As is commonly reported in the literature (Alhassan & Whitt-Glover, 2014;Finch et al, 2014;Herbert et al, 2013), variability in implementation occurred over time for a given teacher and within a given school at any point in time. This variability suggests that classroom-and school-level factors influenced preschool teacher implementation, which we are investigating as a reflection of setting complexity (Craig et al, 2008;Foster-Fishman, Nowell, & Yang, 2007;Hawe, Shiell, & Riley, 2004.…”
Section: Discussionmentioning
confidence: 82%
“…Another study conducted in number of German kindergarten settings noted that children can prepare 'magic fruit plate' twice weekly. Authors then recommended that health promotional activities should increase in preschool children in Germany [22]. The improvement of our preschoolers' knowledge's attested these conclusions.…”
Section: Discussionmentioning
confidence: 96%
“…Study conducted in number of German preschool children found they can prepare 'magic fruit plate' twice weekly. Therefore, it was recommended that health promotional activities should increase in preschool children in Germany (Herbert et al, 2012). In corporation of increase health educational programme and implementation in preschool children has been considered as 'worthy social investments in the human capital of children' (Ling et al, 2014;Duncan and Magnuson, 2013;Obeng, 2010;Logue and Harvey, 2010).…”
Section: Discussionmentioning
confidence: 99%